Persepsi Siswa Program Keahlian Kuliner terhadap Pelaksanaan Uji Kompetensi Keahlian (UKK) - Yuni Muliyana; Rina Febriana; Annis Kandriasari; Constantinus Rudy Prihantoro; Muhammad Nurtanto (Reslaj: Religion Education Social Laa Roiba Journal, 2026)
UKK is an evaluation instrument in vocational high school (Sekolah Menengah Kejuruan/SMK) education used to measure students’ competency achievement in accordance with the needs of the business and industrial sectors. This study aims to describe the perceptions of students in the Culinary Expertise Program regarding the implementation of UKK. The study employed a quantitative approach with a descriptive survey method. The respondents consisted of 19 graduates of the Culinary Expertise Program at SMK Tunas Pembangunan who had participated in UKK. Data were collected online using a closed-ended questionnaire consisting of 24 statement items with a four-point Likert scale. The data were analyzed using descriptive statistics, including frequency, percentage, mean, and standard deviation. The results showed that, in general, students’ perceptions of the implementation of UKK were in the high category, with a mean score of 3.21. The indicator with the highest mean score was the alignment of UKK with the needs of the culinary industry (M = 3.32), while the lowest indicator was industry involvement in UKK assessment (M = 2.93). The findings indicate that the implementation of UKK is considered to be aligned with industry needs and supports students’ work readiness, although industry involvement in the implementation and assessment of UKK still needs to be improved.